Atmospheric-Window-Matching Hierarchical Broadband Infrared Absorber Realized by Lithography-Free Fabrication - Li, Dezhao; Li, Yang; Su, Yu; Chi, Cheng; Huang, Baoling (Frontiers in Energy Research, 2018)
An ultra-broadband selective absorber has been realized with a hierarchical structure through integrating vacuum impedance-matched structure, quarter wavelength structure, and gradient refractive index structure. Through optimizing the design parameters of the proposed hierarchical structure, an ultra-broadband infrared absorber covering the three major atmospheric windows (0.7–2.5, 3–5, and 8–14 μm) has been numerically and experimentally demonstrated. An overall absorption up to 80% covering all the three major atmospheric infrared windows and a ratio of the total absorptions within and beyond the windows as high as 5.88 has been achieved with the developed absorber. The high absorption and spectral selectivity of the absorber make it promising for sensitive broadband infrared spectroscopy detection. The proposed hierarchical structure also provides great design freedom with many tunable factors, making it convenient to extend the design for other applications. In addition, we developed a cost-effective lithography-free method for the fabrication of this structure. The design flexibility and fabrication convenience of this hierarchical structure render it suitable for the development of tailored selective broadband absorbers for targeted applications.